MATHEMATICAL ANALYSIS OF THE INCREASED DEVELOPMENT OF STUDENTS IN HIGHER EDUCATION USING THE INNOVATION CLUSTER OF PEDAGOGICAL EDUCATION - Boltayeva M. D. (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, based on the principle of "Innovative cluster of pedagogical education" and "Study of the economic importance of co-cultivation of soybeans and corn (heard, seen, done)" There is information on raising the level of integration, increasing practical knowledge, the organization of cooperation with higher education and research institutions.